Recent progress in microfiber-optic sensors - Luo, Wei (2021)
Recently, microfiber-optic sensors with high sensitivity, fast response times, and a compact size have become an area of interest that integrates fiber optics and nanotechnology. Distinct advantages of optical microfiber, such as large accessible evanescent fields and convenient configurability, provide attractive benefits for micro- and nano-scale optical sensing. Here, we review the basic principles of microfiber-optic sensors based on a broad range of microstructures, nanostructures, and functional materials. We also introduce the recent progress and state-of-the-art in this field and discuss the limitations and opportunities for future development.